Madonna - Morton, Andrew (London Michael O'Mara Books Ltd., 2001)
Biography of the American singer and actress Madonna (1958), based on research and interviews with friends and family
Include Color Illustration and Index
Keywords: Singers -- United States -- Madonna, 1958- -- Biography